Case reportsSuccessful surgical repair of a chronic left ventricular pseudoaneurysm - Wdowiak-Okrojek, Katarzyna; Lipiec, Piotr; Szewczyk, Monika; Lubiński, Andrzej; D. Kasprzak, Jarosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
A 53-year-old patient, previously in good health condition, was admitted to the Cardiology Department with a history of chest pain and ECG abnormalities suggesting a recent myocardial infarction. Troponin level was not elevated, but the echocardiogram revealed a huge aneurysm with possible wall rupture and thrombus adjacent to the apex. The ejection fraction was very low, estimated for 23%. The magnetic resonance imaging confirmed the primary diagnosis of pseudoaneurysm. Treatment with ACE-i and diuretics was initiated, and the patient was discharged in stable condition. Subsequently, the case was discussed with cardiac surgeons: despite high risk, the patient was qualified for operation. The left ventricle was reconstructed with a bovine pericardial patch using the Menicanti method, and the patient recovered well. The control echocardiogram showed significant improvement of left ventricular contractility with ejection fraction of 35%.